Effect of Marek's vaccine on some lymphoid organs in layers - H. A. Hassan; T. S. Qubih (Iraqi Journal of Veterinary Sciences, 2011)
The aim of the study was to examine experimentally the gross and histological changes in layers (ISA Brown) inoculated with bivalent vaccine (CVI 988 and HVT) intramuscularly at one day of age. Samples of spleen, thymus and bursa of Fabricius were taken at different period post vaccination. Results indicate, gross changes were characterized by atrophy of thymus and congestion, congestion of spleen, with presence of serous fluid in bursa of Fabricius in some samples. Histologically, the spleen at early stage, infiltration of lymphocytes was low and then relatively an increased in number on post vaccination days 13 and 16. Also there was high infiltration of these cells around the splenic artery in addition to their aggregation in the nodes. The bursa of Fabricius showed decreased infiltration of lymphocytes on days 4, 7 and 10, where as these cells increased in infiltration on day 13 after vaccination.